2005
DOI: 10.1146/annurev.neuro.28.061604.135637
|View full text |Cite
|
Sign up to set email alerts
|

Neural Network Dynamics

Abstract: Neural network modeling is often concerned with stimulus-driven responses, but most of the activity in the brain is internally generated. Here, we review network models of internally generated activity, focusing on three types of network dynamics: (a) sustained responses to transient stimuli, which provide a model of working memory; (b) oscillatory network activity; and (c) chaotic activity, which models complex patterns of background spiking in cortical and other circuits. We also review propagation of stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
364
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 454 publications
(390 citation statements)
references
References 76 publications
13
364
0
2
Order By: Relevance
“…The most direct evidence is provided by the work of , Beggs & Plenz (2003 reported critical behavior in slices of cortical tissue, in the form of "avalanches" of neuronal discharges. This type of activity was subsequently also ascertained in intact cortical tissue of primates, and supports the contention that neuronal avalanches are an organizing principle of cell assemblies in cortical tissue (Plenz & Thiagarajan , 2006; for a discussion, see Vogels et al, 2005). The "avalanches" observed by these investigators meet the criteria for Self-organized Criticality which signifies their scale invariance: thus, the extent of neuron assemblies encompasses spatial dimension at any scale, including very large-range connections, potentially covering major expanses of cortical tissue.…”
Section: Dynamics In Dynamic Core and The Global Neuronal Workpacesupporting
confidence: 70%
“…The most direct evidence is provided by the work of , Beggs & Plenz (2003 reported critical behavior in slices of cortical tissue, in the form of "avalanches" of neuronal discharges. This type of activity was subsequently also ascertained in intact cortical tissue of primates, and supports the contention that neuronal avalanches are an organizing principle of cell assemblies in cortical tissue (Plenz & Thiagarajan , 2006; for a discussion, see Vogels et al, 2005). The "avalanches" observed by these investigators meet the criteria for Self-organized Criticality which signifies their scale invariance: thus, the extent of neuron assemblies encompasses spatial dimension at any scale, including very large-range connections, potentially covering major expanses of cortical tissue.…”
Section: Dynamics In Dynamic Core and The Global Neuronal Workpacesupporting
confidence: 70%
“…Moving beyond the issue of brain localization, our commitment to dynamic systems theory also factors in to our emphasis on sustained activation peaks or "bump" attractors (Amari, 1977; see also, e.g., Vogels, Rajan & Abbott, 2005). One advantage to using dynamic field models is that this class of neural networks have been quasi-formally analyzed (Amari, 1977).…”
Section: The Dft Is Grounded By Neural Principlesmentioning
confidence: 99%
“…A number of studies have shown that networks of sparsely connected spiking model neurons can produce highly irregular, chaotic activity without any external source of noise Sompolinsky, 1996, 1998;Brunel, 2000;Mehring et al, 2003;Lerchner et al, 2004;Vogels et al, 2005). These networks allow for the study of signal propagation without the unrealistic injection of external noise.…”
Section: Introductionmentioning
confidence: 99%